The Concept ‘St. Petersburg House’ in the World Picture of Urban Mythology - Mazalova Nataliya E. (Художественная культура)
In this article, the concept ‘St. Petersburg house’, which combines spatial, vital, anthropomorphic and other characteristics, is considered from the standpoint of the anthropological approach. The main features of a St. Petersburg house are highlighted — the time of construction (the 19th — early 20th centuries), durability, solidity, quality, beauty, etc. Other important features of a St. Petersburg house include coziness but not comfort, and it being considered as a book storage. The article touches upon the meanings of ‘house / home’: a house as one’s own space, family, and homeland. The author emphasises the expansion of the space of a St. Petersburg house into the entire city space of St. Petersburg. The metaphors referring to a St. Petersburg house, e.g. ‘a house as a person’, are analysed. The author concludes that the concept ‘St. Petersburg house’ is a complex mental formation associated with the world picture of St. Petersburg mythology and possessing a soul, spirit, style, taste, and ‘Europeanness’.